Digital Museums as Learning Platforms: Assessing Their Impact on Historical Education - Fikri, Asyrul; Bunari, Bunari; Yanuar Al-Fiqri, Yanuar; Yuliska, Yuliska (Pascasarjana UM, 2023)
History represents a set of facts from the past events that were real and genuinely occurred in their time. Historical sources are crucial for reconstructing and generalizing history so that it can be comprehended by students. However, the limited availability of historical sources poses a significant challenge for students when learning history. This limitation can be addressed by utilizing museum websites as learning resources. This study aims to evaluate the effectiveness of museum websites as a learning resource for history education. Research and Development (R&D) methodology was employed in this study. The research sample consisted of 180 high school students selected from a population of 564 students in Pekanbaru City using purposive sampling techniques. Data collection was carried out through observations, expert validation questionnaires, product trial questionnaires, and historical thinking skills tests. The collected data were analyzed quantitatively using t-tests to assess the impact of museum websites as a learning resource for students. The results indicated that the developed museum website was valid and reliable, and the t-test analysis showed a significant impact of the museum website as a history learning resource, with a significance value of 0.000 (less than 0.05).